Survey of reconnection signatures in auroral oval ion precipitation - Sotirelis, Thomas S.; Gjerloev, Jesper W.; Hairston, Marc (Frontiers in Astronomy and Space Sciences, 2023)
The protons and electrons on newly reconnected field lines exhibit time-of-flight effects that have been observed and modelled on both the dayside and nightside, at both high and low altitudes. These reconnection signatures feature proton energy distributions that are cutoff toward low energy. In LEO the cutoff energy exhibits a dispersion with latitude, typically seen in the cusp on the dayside, and referred to as velocity dispersed ion structures (VDIS) on the nightside. Here, an automated algorithm for detecting such low-energy cutoffs (LECs) in the energy spectra of precipitating ions was developed, without regard for any possible dispersion with latitude. The occurrences of LEC ion spectra were mapped over a year of DMSP observations. There are four distinct components to this map, two of which are produced by reconnection. On the dayside LEC ion spectra are seen in cusp, mantle, and open-LLBL precipitation, predominantly at sub-keV energies, as the result of dayside reconnection. On the nightside LEC ion spectra are seen at the poleward edge of the oval at supra-keV energies (usually dispersed with latitude), that indicate magnetotail reconnection. There is another supra-keV population seen on the dusk side at the equatorward edge of the oval, possibly indicating the onset of isotropy. Finally, there is a sub-keV population seen throughout the auroral oval that is thought to consist of ions accelerated out of the opposing hemisphere. The presence of the nightside reconnection signature is modulated by magnetic activity level. Superposed epoch analyses of the ionospheric flow velocity reveal flow through the open–closed boundary when reconnection signatures are present, and enhanced upflow on the dayside when reconnection signatures are present.